IMPLEMENTASI PROGRAM ELEKTRONIK TILANG (E-TILANG) PADA DIREKTORAT LALU LINTAS (DITLANTAS) POLDA SULAWESI UTARA - KRISTIN MANSO; FLORENCE LENGKONG; VERY LONDA (JURNAL ADMINISTRASI PUBLIK, 2022)
The purpose of this study was to find out how the Electronic Ticketing Program Implementationat the Traffic Directorate (Ditlantas) of the North Sulawesi Police. This research uses descriptivequalitative research. Sources of data used in this study are primary data and secondary data withdata collection techniques, namely observation, interviews and documentation. The theory used isthe theory of Smith (2016) which looks at policy implementation from four variables, namely;Ideal Policies, Target Groups, Implementing Organizations and Environmental Factors. Basedon the results of the study, it shows that the implementation of the electronic ticketing program atthe North Sulawesi Regional Police Traffic Directorate has not been running optimally. This isrelated to the constraints seen from the aspects of Idealized Policy, Target Group, andEnvironmental Factors.Keywords: Implementation, Program, Electronic Ticketing